1994
DOI: 10.1115/1.2901812
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Three-Dimensional Analysis of Heat and Fluid Flow in Gas Metal Arc Welding Using Boundary-Fitted Coordinates

Abstract: Computer simulation of three-dimensional heat transfer and fluid flow in gas metal arc (GMA) welding has been studied by considering the three driving forces for weld pool convection, that is the electromagnetic force, the buoyancy force, and the surface tension force at the weld pool surface. Molten surface deformation, particularly in the case of GMA welding, plays a significant part in the actual weld size and should be considered in order to accurately evaluate the weld pool convection. The size and profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Generally, mathematical modeling approaches for describing the phenomena happened during the arc welding and investigating how the process parameters affect the weld quality, have become an essential and systematic technique. A number of researchers [1][2][3][4][5][6][7][8][9][10][11][12] have reported that convection in weld pools can strongly affect the weld bead dimension and the structure of the resultant welds. The early studies regarding weld pool convection have mainly been done through experiments [1][2].…”
Section: Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, mathematical modeling approaches for describing the phenomena happened during the arc welding and investigating how the process parameters affect the weld quality, have become an essential and systematic technique. A number of researchers [1][2][3][4][5][6][7][8][9][10][11][12] have reported that convection in weld pools can strongly affect the weld bead dimension and the structure of the resultant welds. The early studies regarding weld pool convection have mainly been done through experiments [1][2].…”
Section: Introduction:-mentioning
confidence: 99%
“…However, a number of previous researchers considered only the first three forces, but the drag force was not included as the driving force for mathematical model [6,8]. Even the situation has altered greatly with the advent of increasing computer efficiency and better understanding of the physics of welding, only two papers were found as showed by a few people [9][10]. Tsao and Wu [9] first presented a mathematical model employing the vorticity stream function and implicit finite difference method, but ignored the flow induced by the droplet surface interactions and arbitrarily fixed the parameters of volumetric heat source.…”
Section: Introduction:-mentioning
confidence: 99%
“…The plasma arc pressure is assumed to have a radial distribution in the moving rz cylindrical coordinate system for the following form [25]:…”
Section: Normal To the Local Free Surfacementioning
confidence: 99%
“…Ushio and Wu [25] used a boundary-fitted non-orthogonal coordinate system to handle the largely deformed GMA weld pool surface and predicted the area and configuration of weld reinforcement. In their study, the heat delivered by metal transfer was approximated by an internal heat-generation term and the impact of droplets on the weld pool was considered to be a constant force acting on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Tsao and Wu (1988) (3) presented a 2-dimensional heat transfer model in GMAW, while Tekriwal and Mazumder (1988) (4) suggested a 3-dimensional model. Later, Kim and Na (1994) (5) were able to make more accurate temperature distribution estimations through 3-dimensional temperature distribution explanations using boundary-fitted coordinates. The above studies are all explanations of bead on plate welding.…”
Section: Introductionmentioning
confidence: 99%